Stabilin-1 mediates beneficial monocyte recruitment and tolerogenic macrophage programming during CVB3-induced viral myocarditis. (April 2022) - Carai, Paolo; Papageorgiou, Anna Pia; Van Linthout, Sophie; Deckx, Sophie; Velthuis, Sebastiaan; Lutgens, Esther; Wijnands, Erwin; Tschöpe, Carsten; Schmuttermaier, Christina; Kzhyshkowska, Julia; Jones, Elizabeth Anne Vincent; Heymans, Stephane
Abstract: Pathological innate and adaptive immune response upon viral infection may lead to cardiac injury and dysfunction. Stabilin-1 is a scavenger receptor that regulates several aspects of the innate immunity. Whether stabilin-1 affects the inflammatory response during viral myocarditis (VM) is entirely unknown. Here, we assess the role of stabilin-1 in the pathogenesis of VM and its suitability as a therapeutic target. Genetic loss of stabilin-1 increased mortality and cardiac necrosis in a mouse model of human Coxsackievirus B3 (CVB3)-induced myocarditis. Absence of stabilin-1 significantly reduced monocyte recruitment and strongly reduced the number of alternatively activated anti-inflammatory macrophages in the heart, enhancing a pro-inflammatory cardiac niche with a detrimental T lymphocyte response during VM. Yeast two-hybrid screening, confirmed by affinity chromatography, identified fibronectin as a stabilin-1 interacting partner. Absence of stabilin-1 specifically decreased monocyte adhesion on extracellular fibronectin in vitro. Loss of Type III repeats Extra Domain A (EDA) of fibronectin during VM also increased the mortality and cardiac necrosis as in stabilin-1 knockout mice, with reduced monocytic cardiac recruitment and increased T lymphocyte response. Collectively, stabilin-1 has an immune-suppressive role of limiting myocardial damage during VM, regulating anti-inflammatory monocyte-recruitment to the site of inflammation. Graphical abstract: Unlabelled Image Highlights: Stabilin-1 is expressed in myeloid cells in mouse and human viral myocarditis. Loss of stabilin-1 increased mortality and cardiac necrosis in murine viral myocarditis. Stabilin-1 is required for anti-inflammatory macrophage phenotype differentiation. Stabilin-1 influences monocyte recruitment through binding with extracellular fibronectin.